Analisa Jaringan LAN menggunakan Teknologi EtherChannel untuk meningkatkan performa jaringan pada SMU Panca Sakti Jakarta - Toni Sukendar; Mohammad Ikhsan Saputro (Universitas Respati Indonesia, 2019)
Increasing the number of users is one reason for the decline in network quality if you use the same amount of bandwidth. Local different networks are usually connected using a switch. The decline in network quality is due to an increase in the number of users, and this can be overcome by using the concept of utilizing EtherChannel technology. The use of Etherchannel Technology concept consists of two protocol choices namely PagP (Port Agregation Protocol) and LACP (Line Agregation Control Protocol). The purpose of this research is to test the network quality level using the PAgP (Port Agregation Protocol) and LACP (Line Agregation Control Protocol) protocols. Tests carried out using the concept of client-server, and the application used on the server is FTP as a data transfer or data exchange application, while the VLC software is used for video streaming services. The throughput value generated by the PagP protocol is far better than LACP when compared to using FTP services.